THE HISTORICAL DEVELOPMENT OF A DELICT AGAINST THE STATE IN ANCIENT ROME - Prodanov, Nikolaj; Naumovski, Goce A (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Frequently, without any justification, the significance of the Roman criminal law comes second, as a matter which is classified in ius publicum law. As part of Roman public law, many institutes of Roman criminal law considerably confirm that the universality of Roman law is not only reflected in the application of Roman private law but also in Roman public law. The analysis of the concept of Roman criminal law has once again corroborated the character of Roman law as a scientific discipline, as “anatomy” and the foundation of contemporary law. Roman criminal law, especially the provisions of Justinian’s legislation, is a kind of “speculum iuris”, i.e. the “legal mirror” of the criminal law in Antica, created as an attempt to protect the law in general. Аs Ulpian stresses: Iuris praecepta sunt haec: honeste vivere, alterum non laedere, suum cuique tribuere.